2011
DOI: 10.1163/157006611x604760
|View full text |Cite
|
Sign up to set email alerts
|

Spiritist Mediumship as Historical Mediation: African-American Pasts, Black Ancestral Presence, and Afro-Cuban Religions

Abstract: The scholarship on Afro-Atlantic religions has tended to downplay the importance of Kardecist Espiritismo. In this article I explore the performance of Spiritist rituals among Black North American practitioners of Afro-Cuban religions, and examine its vital role in the development of their religious subjectivity. Drawing on several years of ethnographic research in a Chicago-based Lucumí community, I argue that through Spiritist ceremonies, African-American participants engaged in memory work and other transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Instead of seeing artifacts and archives as products of one decipherable ephemeral moment, we can instead decipher how objects like spirit dolls, beaded vessels, offerings at altars, and scribbles in notebooks provide invitations for revisiting and renegotiating spiritual connections repeatedly (Turner ). These relationships are intimate and rely on affective bonds that are relational in nature yet deeply entrenched in the textures of racial historical memory (Espírito Santo ; Pérez ; Wirtz ).…”
Section: Resultsmentioning
confidence: 99%
“…Instead of seeing artifacts and archives as products of one decipherable ephemeral moment, we can instead decipher how objects like spirit dolls, beaded vessels, offerings at altars, and scribbles in notebooks provide invitations for revisiting and renegotiating spiritual connections repeatedly (Turner ). These relationships are intimate and rely on affective bonds that are relational in nature yet deeply entrenched in the textures of racial historical memory (Espírito Santo ; Pérez ; Wirtz ).…”
Section: Resultsmentioning
confidence: 99%
“…From a different angle, the found clusters point to strong links between thankfulness and spiritual well-being and the other positive psychology variables. Several research ( 89 92 ) have shown correlations between religion, well-being, stress management, and happiness. Many additional studies have also shown a link between spirituality and dimensions of subjective well-being including life satisfaction, optimism, self-esteem, and the sense of having lived a meaningful life ( 93 – 97 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than a spirit completely taking over the medium or the medium completely losing consciousness, the process of spirit possession is one of knowledge production whereby, by incorporating the spirit and becoming a more malleable 'selfless' self, the medium emerges from the encounter with the spirit with new ways of knowing and seeing and alternative interpretive schema. In opposition to the grand narratives of colonial authorities, Pérez (2011) argues that spirit possession offers a way to recreate the past in communal settings, contributing to the emergence of "counter-memories" (Stoller, 1997) and lost voices. Through these re-imaginings, the 'background' of certain histories are brought to the fore.…”
Section: 'Doublementioning
confidence: 99%